Effect of sewage sludge ash on mechanical and microstructural properties of geopolymers based on metakaolin - Istuque, D. B. [UNESP] (2019)
This paper explored the effect of sewage sludge ash (SSA) on the mechanical and microstructural properties of geopolymers based on metakaolin (MK) involving two different SiO 2 /Na 2 O molar ratios (0.8 and 1.6), two temperature curing conditions (25 °C and 65 °C) and various ages of curing (1, 3, 7, 14, 28, 90 or 180 days). The geopolymers were characterized using different techniques as X-ray diffraction (XRD), thermogravimetric analysis (TGA), Fourier transform infrared spectroscopy (FTIR), Scanning Electron Microscopy (SEM) and compressive strength of mortars. The compressive strength tests showed that the replacement of MK by SSA in 10 wt% when cured at 25 °C with the highest SiO 2 /Na 2 O molar ratio reaches similar compressive strengths after 14 days of curing compared to the samples with only MK, which reached a maximum compressive strength of 50.8 MPa at 180 days. The FTIR analyses carried out in the geopolymer pastes with SSA (10 wt% of SSA and 90 wt% of MK) showed a formation of N-A-S-H gels in the samples cured at 25 °C. The microstructural studies by XRD, TGA and SEM pointed out the formation of a crystalline phase as Na P-type zeolite in MK/SSA based-geopolymer pastes cured at 65 °C, which explained the loss of compressive strength of the samples cured at high temperature. However, the SSA retarded the crystallization process in the MK based-geopolymer.